How attitude toward the behaviour, perceived credibility and perceived control affect mobile virality in Johor - Helmee, Rabi’atul’ Adawiyah (2018)
This study was attempted to investigate the attitude towards the behaviour, perceived control and perceived credibility towards mobile virality. The purpose of this research is to identify and examine whether attitude towards behaviour, perceived credibility and perceived control will affect mobile virality in Malaysia. Pilot testing was carried out to certify the reliability of the questions before final distribution. There are a total of 132 sets of questionnaires being distributed to employees in Kawasan Perindustrian Tebrau 1 in Johor. This research is a quantitative research which had used the self-administered electronic questionnaire as the instrument for the data collection. The data was collected and viable at a percentage 85.60% out of the possible 132 respondents which was derived from the total population of 200 elements. Sample selection was based on convenience sampling method. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 20 software. Using SPSS, numerous tests were converged such as reliability analysis, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regression analysis. The results indicated that viral marketing, which include attitude toward behaviour, perceived control and perceived credibility, are related to mobile virality.